Cancer & Metabolism - Pollak, Michael; Vander Heiden, Matthew
Cancer & Metabolism welcomes studies on all aspects of the relationship between cancer and metabolism, including: Molecular biology and genetics of cancer metabolism Whole-body metabolism, including diabetes and obesity, in relation to cancer Metabolomics in relation to cancer; Metabolism-based imaging Preclinical and clinical studies of metabolism-related cancer therapies.